Perception of facial emotions. - Yeo, Shu Hui. (2013)
Facial emotions are the main expressers and communicators of internal state and affect. Specific domains of perception of facial emotions are examined – biological aspects, cultural aspects and changes throughout the lifespan. Following that, we will explore research on dysfunction and abnormalities in perception of facial emotions that accompany a variety of neuropsychological conditions – schizophrenia, Alzheimer’s disease and autism spectrum disorder. Finally, we will look into face viewpoint and gaze direction and its influence on perception of facial emotions. Conclusions are drawn about the linkages between the different domains.